Comparison of ultrasonography and fluoroscopy as guides for extracorporeal shock wave lithotripsy in nephrolithiasis patients: a systematic review (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Extracorporeal shock wave lithotripsy (ESWL) is one of the first-line treatment options for patients with renal stones <2 cm. The large variability in ESWL results may be due to the stone visualization methods using ultrasonography (USG), fluoroscopy, or a combination of both. This study aimed to review the efficacy and safety of the stone visualization method on the stone-free rate (SFR) and postprocedural complications in nephrolithiasis patients. METHODS We conducted a systematic review of USG and fluoroscopy on ESWL until July 2022, based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We assessed and collected summaries of the screened papers. The main outcomes assessed were the SFR of renal stones and postprocedural complications between imaging modalities. RESULTS A total of 7 studies were assessed, including 6 comparative assessments of USG versus fluoroscopy and 1 comparative assessment of USG and fluoroscopy versus fluoroscopy only. Although all studies showed that USG had a higher SFR than fluoroscopy, only 1 study showed a significant difference (p = 0.008). Additionally, superior results were obtained using a combination of USG and fluoroscopy compared with fluoroscopy only. Most studies agreed that USG was not inferior in post-ESWL complication results. CONCLUSIONS Overall, the use of USG is comparable to fluoroscopy because it does not provide a significant difference in the SFR and complications. In most cases, USG is preferred because of the absence of radiation. The combination of fluoroscopy and USG also provides more promising results than a single modality.